The Impact of Exchange Rate on Economic Growth #x2013; Case Studies of Countries in the Asean Region (Global Journal of Management and Business Research, 2020)
The study reflects the impact of an effective multilateral exchange rate in the 1989-2018 period on the economic growth rate of 5 ASEAN countries, including Vietnam, Indonesia, Singapore, Philippines, and Malaysia. To estimate this model, the author uses the Fixed Effects and Random Effects panel data estimation method. Hausman test shows the model calculated using the Fixed Effects method is more suitable than the Random Effects method. In the estimation model, however, heteroskedasticity and autocorrelation came using the Fixed Effects method. Using Prais-Winsten (PCSE) process, the authors overcame the phenomenon
Keywords: exchange rate; economic growth; multilateral exchange rate